PRODUCTIVITY OF USING AUTHENTIC MATERIALS IN TEACHING ENGLISH IN NON-PHILOLOGICAL FACULTIES - Matyokubova Shokhida Abiyrovna (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, we will talk about the methods of using authentic materials in English teaching lessons, besides the types of authentic materials, and the results that can be obtained from these lessons in order to enrich the lessons, especially in the teaching of non-philological faculty students, in order to plan interesting English lessons. It is said that the role of the resources used in the course of the lesson is important in increasing the interest of non-literary faculty students in foreign languages and increasing their motivation to learn the language.